Unidad de capacitación y estudios hidrológicos de la región del Sumapaz plan parcial Sakúku: territorio de memoria e identidad (Sibate-Cundinamarca) (2018)
The following study is focused on the analysis of the Sibaté territory, where a Master Plan is proposed in accordance with the Regional and Sub-regional determinants, having as reference zones, the municipal urban area and the Muña Reservoir with recovery projection to 2050, and proposing a Partial Plan for the edge of the city to delimit the growth of the city and proposing projects on that border, which are of regional impact and which go hand in hand with the environmental recovery of the ecological structure of the municipality. After carrying out a physical inventory within the 3 scales of study (functional, environmental and socio-economic) comprising the provinces of Soacha, Sumapáz and the south of Bogotá, areas that comprise the Sumapáz paramo as a diagnosis the lack of articulation of the great environmental element to the different provinces, and the mono-function in which the different provinces develop economically, in addition to the advanced environmental deterioration caused by mining and harmful agriculture in the vicinity of the foothills of the paramo, in addition to this transportation and the road infrastructure is deficient.